Tumour endothelial marker 1/endosialin-mediated targeting of human sarcoma. (February 2018) - Guo, Y.; Hu, J.; Wang, Y.; Peng, X.; Min, J.; Wang, J.; Matthaiou, E.; Cheng, Y.; Sun, K.; Tong, X.; Fan, Y.; Zhang, P.J.; et al.
Abstract: Background: Tumour endothelial marker 1 (TEM1/endosialin/CD248) is a tumour-restricted cell-surface protein expressed by human sarcomas. We previously developed a high-affinity human single-chain variable fragment (scFv)-Fc fusion protein (78Fc) against TEM1 and demonstrated its specific binding to human and mouse TEM1. Patient and methods: Clinical sarcoma specimens were collected between 2000 and 2015 at the Hospital of the University of Pennsylvania, as approved by the institutional review board and processed by standard formalin-fixed paraffin embedded techniques. We analysed TEM1 expression in 19 human sarcoma subtypes (n = 203 specimens) and eight human sarcoma–cell lines. Near-infrared (NIR) imaging of tumour-bearing mice was used to validate 78Fc binding to TEM1 + sarcoma in vivo . Finally, we tested an immunotoxin conjugate of anti-TEM1 78Fc with saporin (78Fc-Sap) for its therapeutic efficacy against human sarcoma in vitro and in vivo . Results: TEM1 expression was identified by immunohistochemistry in 96% of human sarcomas, of which 81% expressed TEM1 both on tumour cells and the tumour vasculature. NIR imaging revealed specific in vivo targeting of labelled 78Fc to TEM1 + sarcoma xenografts. Importantly, 78Fc-Sap was effective in killing in vitro TEM1 + sarcoma cells and eliminated human sarcoma xenografts without apparent toxicity in vivo . Conclusion: TEM1 is an important therapeutic target for human sarcoma, and the high-affinity TEM1-specific scFv fusion protein 78Fc is suitable for further clinical development for therapeutic applications in sarcoma. Highlights: Tumour endothelial marker 1 (TEM1)/endosialin is a novel tumour target highly expressed in sarcoma and many tumours. The article shows TEM1 is expressed in sarcoma (96%, n=203), and the pre-clinical development of a novel anti-TEM1 antibody. We demonstrated the anti-tumour activity of the antibody drug conjugate against cancer cell lines in vitro and in vivo. In addition, we show preliminary toxicology results and a possible mechanism of molecular escape. These data represents a key milestone towards the clinical development of TEM1-targeted imaging and therapy.